Birth spacing, fertility and neonatal mortality in India: dynamics, frailty and fecundity - Sonia Bhalotra; Arthur van Soest (Institute for the Study of Labor (IZA), 2006)
A dynamic panel data model of neonatal mortality and birth spacing is analyzed, accounting for causal effects of birth spacing on subsequent mortality and of mortality on the length of the next birth interval, while controlling for unobserved heterogeneity in mortality (frailty) and birth spacing (fecundity). The model is estimated using micro data on almost 30,000 children of 7,300 Indian mothers, for whom a complete retrospective record of fertility and child mortality is available. Information on sterilization is used to identify an equation for completion of family formation that is needed to account for right-censoring in the data. We find clear evidence of frailty, fecundity, and causal effects of birth spacing on mortality and vice versa, but find that birth interval effects can explain only a limited share of the correlation between neonatal mortality of successive children in a family. We also predict the impact of mortality on total fertility. Model simulations suggest that, for every neonatal death, an additional 0.37 children are born, of whom 0.3 survive.
Keywords: I12; J13; C33; 330; fertility; birth spacing; neonatal mortality; health; dynamic panel data models; siblings; Fruchtbarkeit; Kindersterblichkeit; Indien